ASSESSMENT OF KNOWLEDGE ABOUT TEAMWORK AMONG NURSES - PERVAIZ, M; SHARIF, N; ZUNAIRA, .; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Teamwork is essential in healthcare, particularly among nurses who are crucial in patient care. Effective teamwork has been shown to improve patient safety, care quality, and healthcare outcomes. Objective: This study aimed to assess the level of teamwork knowledge among nurses at the Punjab Institute of Neurosciences (PINS) in Lahore, Pakistan, and to examine factors influencing this knowledge, including years of experience, education level, and previous teamwork training. Methods: This cross-sectional study was conducted with a sample of 100 registered nurses at PINS. Data were collected using a structured questionnaire assessing demographics and teamwork knowledge across domains such as communication, role clarity, conflict resolution, and interprofessional collaboration. Statistical analyses, including ANOVA and t-tests, were conducted to explore associations between teamwork knowledge and demographic factors. Results: The findings indicated a moderate overall teamwork knowledge score among nurses, with strengths in communication (mean score: 3.8) and interprofessional collaboration (mean score: 3.9). However, areas like conflict resolution (mean score: 3.2) and role clarity (mean score: 3.5) showed room for improvement. Higher levels of education, more years of experience, and previous teamwork training were significantly associated with greater teamwork knowledge. Nurses with advanced degrees and those who had received teamwork training scored notably higher than their peers without such training. Conclusion: The study highlights the influence of education, experience, and targeted teamwork training on nurses’ teamwork knowledge. Recommendations include implementing regular teamwork training programs, mentorship initiatives for junior nurses, and department-specific training to strengthen teamwork competencies. Future research should focus on the impact of teamwork knowledge on patient outcomes, providing insights into how enhancing teamwork skills can improve healthcare quality in Pakistan.